Deteksi Gen Ketahanan Terhadap Powdery Mildew Pada Melon (Cucumis melo L. ‘Aramis’) - Budi Setiadi Daryono; Hani Christin Yambise (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2018)
Melon (Cucumis melo L.) usually used as a fresh fruit, which contained high vitamin C and in Indonesia melon is one of the favorite fruit. Indonesia is a country that has a high biodiversity. One of the potential strategies in order to improve productivity and quality of crops competitiveness is through plant breeding. This study used melon Aramis from PT East West Seed Indonesia hybrid melon from crosses between 7319 (F) with 7347 (M). The research aims to determine the phenotype character of melon cultivar Aramis and to detect powdery mildew resistance gene. The research is conducted in Pusat Inovasi Agro Teknologi (PIAT UGM) Yogyakarta and at the Laboratory of Genetics and Breeding Faculty of Biology, Universitas Gadjah Mada. Resistance genes detection is conducted by Sequence Characterized Amplified Regions method (SCARs) using PCR and showed negative result of Aramis cultivar on detection of gene resistance to powdery mildew.